Review and Evaluation of Hydrogen and Air Heat Exchangers for Fuel Cell-Powered Electric Aircraft Propulsion - Sahil Bhapkar; Chetan Sain; Stefan Kazula (Engineering Proceedings, 2025)
Hydrogen fuel cell systems are a viable option for electrified aero engines due to their efficiency and environmental benefits. However, integrating these systems presents challenges, notably in terms of overall system weight and thermal management. Heat exchangers are crucial for the effective thermal management system of electric propulsion systems in commercial electrified aviation. This paper provides a comprehensive review of various heat exchanger types and evaluates their potential applications within these systems. Selection criteria are established based on the specific requirements for air and hydrogen heat exchangers in electrified aircraft. The study highlights the differences in weighting criteria for these two types of heat exchangers and applies a weighted point rating system to assess their performance. Results indicate that extended surface, microchannel, and printed circuit heat exchangers exhibit significant promise for aviation applications. The paper also identifies key design challenges and research needs, particularly in enhancing net heat dissipation, increasing compactness, improving reliability, and ensuring effective integration with aircraft systems.